Epidemiological-Clinical Profile and Magnetic Resonance Imaging (MRI) of Endometriosis in Kinshasa (2022–2023) - Félix Dibazola Mbambi; Cynthia Minouche Bukumba; Stéphane Yanda Tongo; Nodi Botshele Letumu; Frederick Tshibasu Tshienda; Tacite Kpanya Mazoba; Doudou Batumbo Boloweti; Richard Ekila Ifinji; Pierre Lwamba Simanyama; Antoine Molua Aundu; Jean Tshibola Mukaya; Gertrude Luyeye Mvila (Orapuh Journal)
Introduction